2016
DOI: 10.1113/jp272032
|View full text |Cite
|
Sign up to set email alerts
|

AMP‐activated protein kinase inhibits Kv1.5 channel currents of pulmonary arterial myocytes in response to hypoxia and inhibition of mitochondrial oxidative phosphorylation

Abstract: Key points Progression of hypoxic pulmonary hypertension is thought to be due, in part, to suppression of voltage‐gated potassium channels (Kv) in pulmonary arterial smooth muscle by hypoxia, although the precise molecular mechanisms have been unclear.AMP‐activated protein kinase (AMPK) has been proposed to couple inhibition of mitochondrial metabolism by hypoxia to acute hypoxic pulmonary vasoconstriction and progression of pulmonary hypertension.Inhibition of complex I of the mitochondrial electron transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 83 publications
2
40
0
Order By: Relevance
“…Interestingly, we found that K V channel blockade by 4‐aminopyridine augmented PORH Amplitude in non‐glabrous forearm skin (Figure B), suggesting that K V channels may partly restrict PORH. Since hypoxia reportedly inhibits K V channels thereby causing vasoconstriction, arterial occlusion‐induced local hypoxia might have caused a similar response in the present study, explaining why K V channel blockade augmented PORH Amplitude. However, given the Area under the curve was unaffected by 4‐aminopyridine (Figure E), the restricting effect of K V channels, if any, appears to occur at the beginning of the PORH response only.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, we found that K V channel blockade by 4‐aminopyridine augmented PORH Amplitude in non‐glabrous forearm skin (Figure B), suggesting that K V channels may partly restrict PORH. Since hypoxia reportedly inhibits K V channels thereby causing vasoconstriction, arterial occlusion‐induced local hypoxia might have caused a similar response in the present study, explaining why K V channel blockade augmented PORH Amplitude. However, given the Area under the curve was unaffected by 4‐aminopyridine (Figure E), the restricting effect of K V channels, if any, appears to occur at the beginning of the PORH response only.…”
Section: Discussionsupporting
confidence: 70%
“…Whereas NO acts as both a target and an effector of the AMPK pathway in endothelial cells (Fisslthaler & Fleming, 2009;Suzuki et al, 2008), less is known about the mechanism by which NO regulates AMPK in smooth muscle cells. Moreover, data on the role of AMPK in vascular proliferation and pulmonary hypertension are conflicting (Agard et al, 2009;Dean, Nilsen, Loughlin, Salt, & MacLean, 2016;Ibe et al, 2013;Moral-Sanz et al, 2016;Salt & Hardie, 2017;Song et al, 2016). Several studies have shown that AMPK promotes SMC proliferation and the development of pulmonary hypertension, which was reversed with AMPK inhibition (Ibe et al, 2013;Moral-Sanz et al, 2016).…”
Section: F I G U R Ementioning
confidence: 99%
“…Moreover, data on the role of AMPK in vascular proliferation and pulmonary hypertension are conflicting (Agard et al, 2009;Dean, Nilsen, Loughlin, Salt, & MacLean, 2016;Ibe et al, 2013;Moral-Sanz et al, 2016;Salt & Hardie, 2017;Song et al, 2016). Several studies have shown that AMPK promotes SMC proliferation and the development of pulmonary hypertension, which was reversed with AMPK inhibition (Ibe et al, 2013;Moral-Sanz et al, 2016). Conversely, other studies have shown that AMPK activation reduced SMC proliferation and vascular remodeling and may be protective against the development of hypoxia-induced pulmonary hypertension (Agard et al, 2009;Dean et al, 2016;Song et al, 2016).…”
Section: F I G U R Ementioning
confidence: 99%
“…Furthermore, as noted above, the fact that AMPK is a serine threonine kinase suggested the capacity for regulation of processes outside of metabolism such as ion channel activity ( Figure 1), which our findings (Evans et al, 2005c;Ikematsu et al, 2011;Ross et al, 2011) and those of others have since confirmed. For example, AMPK may phosphorylate and "inactivate" the pore forming alpha subunit of multiple Ca 2+activated potassium channels (KCa1.1 and KCa3.1) (Klein et al, 2009;Ross et al, 2011), the voltage-gated potassium channel Kv1.5 (Andersen et al, 2015;Mia et al, 2012;Moral-Sanz et al, 2016) and the ATP-inhibited KATP channel (Kir6.2) (Chang et al, 2009), or may phosphorylate and "activate" Kv2.1 alpha subunits . Thereby AMPK has the potential to increase or decrease cell excitability, in a manner determined by both the cell-specific expression of its subunits and members of the ion channel superfamily, providing the capacity for system-level adjustments to whole-body metabolic status (Evans, 2006a).…”
Section: The Amp-activated Protein Kinasementioning
confidence: 99%